Immunology Aspects in Tension-Type Headache Chronicity - Restu Susanti (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2020)
Tension-Type Headache (TTH) headache is a type of primary headache which mostlycomplained by patients. The pain often ignored due to low mortality rates. Inadequatemanagement makes the pain becoming chronic and causing a high disability rate. Many factorsinvolved in transforming infrequent tension-type headache to chronic tension-type headache.A deeper understanding of the immune system's role in the pathophysiological process andmodulation of chronic pain could be a potential target for developing therapies in managingchronic pain.